2014
DOI: 10.1016/j.proeng.2014.10.464
|View full text |Cite
|
Sign up to set email alerts
|

Study and Prediction for the Fire Resistance of Acid Corroded Intumescent Coating

Abstract: Acid corrosion may cause the deterioration of the fire resistance of the intumescent fire retardant coatings, especially for the coatings used in the acid polluted environment. This paper reported the results of an experimental study of degradation in fire protection performance of intumescent coating for steel elements after different times of immersion in the hydrochloric acid solution. After acid erosion, the thickness of the coating thinned, the surface became rough and had cracks and broken holes. The siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Ji et al conducted a fire-resistance test in small-scale testing furnace. In this setup, two thermocouples were attached to measure the back side temperature and to monitor the furnace temperature [30]. Similarly, Cutter et al developed a novel small-scale fire-resistance test method.…”
Section: Fire-resistance Furnacesmentioning
confidence: 99%
“…Ji et al conducted a fire-resistance test in small-scale testing furnace. In this setup, two thermocouples were attached to measure the back side temperature and to monitor the furnace temperature [30]. Similarly, Cutter et al developed a novel small-scale fire-resistance test method.…”
Section: Fire-resistance Furnacesmentioning
confidence: 99%
“…The coating becomes uneven and thin, with large pore size and cracks, holes and rough surface morphology, and decreases fire-resistant performance of coating after acid corrosion. 178,179…”
Section: Influence Of Weathering On the Performance Of Intumescent Comentioning
confidence: 99%
“…Despite their versatility, manufacturability in the application, aesthetic characteristics, intumescent-type coatings have a series of disadvantages. First of all, it is low atmosphere resistance [3] and resistance to aggressive environments [4], and, accordingly, a limited service life [5]. The authors of work [6], for example, found that after 30 years of natural aging under the climatic conditions of Italy, intumescent coatings lose their fire protection functions completely.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily due to the lack of procedures for modeling the conditions of artificial aging for a coating. There are also no adequate criteria for determining the fire-protective properties of the coating after aging, followed by forecasting its service life [4,5]. National and international standards, for example [20], to some extent define methodological approaches to determining the durability of reactive coatings.…”
Section: Introductionmentioning
confidence: 99%